Sistem Pakar Deteksi Kerusakan Truk Mitsubishi Fuso Berbasis Desktop - Heri Pratama; Sofika Enggari; Irzal Arief Wisky (Jurnal Teknologi, 2021)
An expert system is a computer program that can mimic the thought process and expert knowledge in solving a particular problem. The implementation of this expert system is widely used in the field of artificial intelligence because expert systems are seen as a way of storing expert knowledge in certain fields in computer programs so that decisions can be made in making intelligent reasoning on a specific problem in this case the problem of detecting damage to Mitsubishi trucks. Fuso at Berdikari Motor Sibolga workshop.